Insights on Antimicrobial Peptides - Enany, Shymaa; Masso-Silva, Jorge; Savitskaya, Anna (IntechOpen, 2022)
Modern medicine is impossible without antibiotics, but global antibiotic usage has led to the development of increasing numbers of multi-drug resistant (MDR) bacteria. Thus, we still have problems with infectious disease treatment despite an arsenal of antibiotics. This has forced researchers to develop new drugs that will be effective against resistant bacteria. Some of these prospective molecules are antimicrobial peptides (AMPs), which are an important component of the innate immune system of various organisms in nature. Currently, more than 3,000 AMPs have been reported with different activities against different bacterial species including resistant phenotype bacteria. AMPs display remarkable structural and functional diversity that is not completely understood. As such, this book presents a comprehensive overview of AMPs and their mechanism of action against MDR bacteria.